Implementation of a neuromuscular training programme in female adolescent football: 3-year follow-up study after a randomised controlled trial - Lindblom, H.; Walden, M.; Carlfjord, S.; Hägglund, M. (British Journal of Sports Medicine, 2014)
Background: Neuromuscular training (NMT) has been shown to reduce anterior cruciate ligament injury rates in highly structured clinical trials. However, there is a paucity of studies that evaluate implementation of NMT programmes in sports.